Penyusunan Jadwal Induk Industri dengan Menggunakan Metode Simpleks Guna Meminimalkan Biaya Produksi - Murti Astuti; Ifa Yuliana (Jurnal Teknik Industri, 2001)
PT. Industri Sandang Nusantara Pata! Secang Magelang is some factory that regarding in manufactur sector which thread producting. For this time the factory have a problem with stacking same kind of product and in the other way less  another product. This case cause that factory use product scheduling based on experience and reckoned of selling in last period.  Connected with this problem, the  case is how to make a good  schedule in order that  factory could be completing consumer demand and decided some main product schedule with simpleks methode.The articulate in factory for this time is reguler employee 65 persons.  If reguler employee is  not enaugh, then there are overtime job (maximal 2 hour/days), and if still  not enaugh too, then used subcontract. Based on capacity of production, the  number of  maximal employee  are 70 personsAccording to  teoritis,  with  using  of  forecasting  and  agregat  planning,  the  factory's problem can be done. This forecasting used to productin supossing in about to many periods.  With use simpleks methode can be planning the number of employee. In order that, the main production can be made.Analyst result get that  demand fluktuation for R 30/1,   PR 30/1  products use Moving Average Linear Trend (3) methode, R 24/ 1,  R I 11,  PR 40/l products using Moving Average Linear Trend (5) methode, PR 45/l  product using Linear Regression methode. Value analyst with based on forecasting result for future 12  periods,  supposed that factory will  pay for Rp.  460.340.000,• After applying Linear Programming giftotal cost Rp. 450.164.576,-.  Thrifting Rp. 10.175.424,- or 2,2%.   Sensitivity analyst made cost to be Rp. 448.651.040,-,   thrifting Rp.  11.688.960,-    or 2,5%  at the number of regular employees 66 persons.